The RAYMOND simulation package — Generating RAYpresentative MONitoring Data to design advanced process monitoring and control algorithms - Gins, Geert; Vanlaer, Jef; Van den Kerkhof, Pieter; Van Impe, Jan F.M. (Computers & chemical engineering, 2014)
•New modular simulation package, implemented in MATLAB, freely downloadable.•Easy implementation of custom models, controls strategies, sensor properties.•Free specification of process variability and process disturbances.•Inclusion of process variability is important for process monitoring and control. This work presents the RAYMOND simulation package for generating RAYpresentative MONitoring Data. RAYMOND is a free MATLAB package and can simulate a wide range of processes; a number of widely-used benchmark processes are available, but user-defined processes can easily be added. Its modular design results in large flexibility with respect to the simulated processes: input fluctuations resulting from upstream variability can be introduced, sensor properties (measurement noise, resolution, range, etc.) can be freely specified, and various (custom) control strategies can be implemented. Furthermore, process variability (biological variability or non-ideal behavior) can be included, as can process-specific disturbances. In two case studies, the importance of including non-ideal behavior for monitoring and control of batch processes is illustrated. Hence, it should be included in benchmarks to better assess the performance and robustness of advanced process monitoring and control algorithms.